Pendekatan Situasional Mengajar Bahasa Inggris Maritim Di Politeknik Pelayaran Sulawesi Utara - Aliong Silalahi (Airman: Jurnal Teknik dan Keselamatan Transportasi, 2022)
English communication skills in the areas of speaking, listening, reading, and writing. However, in many students' minds communication means only interaction between the speaker and the listener. Teaching English at maritime universities and nautical colleges involves not only teaching the language and the sea-related terminology but also making the students aware of the cross-cultural issues and problems that they may encounter in their work onboard ships. The best way of teaching is, how the teacher, instructor, and lecturer can choose and use the right teaching method. FAIES is one of the unique and well-known methods in teaching which can adapt to many situations in the classroom and makes the students feel easy to understand and study comfortably during the lesson especially in speaking English. According to Freud in Wollheim (1981), FAIES (First Aid in English System) is the teaching method to emphasize or stress communication, which consists of a directional approach, functional approach, situational approach, and drilling technique. Maritime English is largely restricted to IMO Standard Marine Communication Phrases, which build basic knowledge of English and had been drafted in a simplified version of maritime English. In terms of maritime education, the current simulator-based studies can be divided into two areas: marine engineering and nautical science. In particular, human factor specialists work in these two fields addressing issues concerning the relationship between humans and technology, such as simulators (Lützhöft et al. 2017). A multitude of new methodologies has been explored and discussed in recent years in an attempt to approach the training and testing of the proficiency of maritime English that meets the international standards laid out in STCW.